2008
DOI: 10.1111/j.1445-6664.2008.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Root system architecture and its relationship to the vegetative reproduction function in horsenettle (Solanum carolinense)

Abstract: Horsenettle (Solanum carolinense L.) is a weed species that can spread via the root system and root fragments. This study investigated the developmental pattern of the subterranean system of horsenettle in an experimental plot containing plastic plates that limited the radial growth of the individual plants in each section of the plot.The vertical architecture of the root system in the 10 month old and 16 month old plants was elucidated by excavating the plants from the experimental plot. The root system consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Solanum carolinense is a clonal perennial weed native to the eastern United States and is invasive in parts of North America and Asia (Bassett and Munro , Miyazaki ). It primarily colonizes disturbed fields and roadsides (Miyazaki ) and hosts a large arthropod community, including L. juncta (Chrysomelidae) and Manduca sexta (Sphingidae) (Wise ). Clonal lines of S. carolinense were obtained from natural populations in north Florida and Georgia (Appendix : Table S1); before use in this study, they were propagated for 3 yr in the glasshouse.…”
Section: Methodsmentioning
confidence: 99%
“…Solanum carolinense is a clonal perennial weed native to the eastern United States and is invasive in parts of North America and Asia (Bassett and Munro , Miyazaki ). It primarily colonizes disturbed fields and roadsides (Miyazaki ) and hosts a large arthropod community, including L. juncta (Chrysomelidae) and Manduca sexta (Sphingidae) (Wise ). Clonal lines of S. carolinense were obtained from natural populations in north Florida and Georgia (Appendix : Table S1); before use in this study, they were propagated for 3 yr in the glasshouse.…”
Section: Methodsmentioning
confidence: 99%
“…The taproot can reach a depth of 240 cm and the roots grow horizontally in soil depths up to 45 cm and become several metres long (Ilnicki & Fertig, 1962). Miyazaki (2008) demonstrated that different sections of the root system had different functions: the bending part forms new shoots; the horizontal part extends into the surrounding area; and the vertical part is used for storage. Shoots are produced from adventitious root buds.…”
Section: Generalmentioning
confidence: 99%
“…Solanum carolinense propagates by creeping roots and seeds. The extensive root system consists of a taproot and horizontally growing roots (Ilnicki & Fertig, 1962; Miyazaki, 2008). The taproot can reach a depth of 240 cm and the roots grow horizontally in soil depths up to 45 cm and become several metres long (Ilnicki & Fertig, 1962).…”
Section: Biology and Ecologymentioning
confidence: 99%
“…Creeping perennials are distinguished by having creeping roots, rhizomes, or stolons that elongate and produce new plants from reproductive buds on these organs (Anderson, 1999). The most serious and uncontrollable species are those that develop extensive underground network systems of either rhizomes with determinate buds at the nodes or creeping roots that produce adventitious buds (Ito, 2020; Ito, Inoue, & Ide, 1966; Ito, Takagi, & Yoshino, 2005; Miyazaki, 2008; Tominaga, 2007; Yukinaga, Ide, Ito, & Shimada, 1975). Typical weed species include Solidago altissima , Artemisia indica spp.…”
Section: Introductionmentioning
confidence: 99%